Learning Linux Shell scripting : unleash the power of Shell scripts to solve real-world problems by breaking through the practice of writing tedious code /: unleash the power of Shell scripts to solve real-world problems by breaking through the practice of writing tedious code. (2015) - Naik, Ganesh Sanjiv
No abstract available